Development of Hemispherical 3D Models of Human Brain and B Cell Lymphomas Using On-Chip Cell Dome System - Ryotaro Kazama; Rina Ishikawa; Shinji Sakai (Bioengineering)
Lymphocytes are generally non-adherent. This makes it challenging to fabricate three-dimensional (3D) structures mimicking the three-dimensional lymphoma microenvironment in vivo. This study presents the fabrication of a hemispherical 3D lymphoma model using the on-chip Cell Dome system with a hemispherical cavity (1 mm in diameter and almost 300 µm in height). Both the human brain lymphoma cell line (TK) and human B cell lymphoma cell line (KML-1) proliferated and filled the cavities. Hypoxic regions were observed in the center of the hemispherical structures. CD19 expression did not change in either cell line, while CD20 expression was slightly upregulated in TK cells and downregulated in KML-1 cells cultured in the Cell Dome compared to those cultured in two-dimensional (2D) flasks. In addition, both TK and KML-1 cells in the hemispherical structures exhibited higher resistance to doxorubicin than those in 2D flasks. These results demonstrate the effectiveness of the on-chip Cell Dome for fabricating 3D lymphoma models and provide valuable insights into the study of lymphoma behavior and the development of new drugs for lymphoma treatment.